Investigation of ZnO nanostructures: Effect of metal and spinning speed on the physical properties - Benhaliliba, M.; Benouis, C.E.; Aida, M.S.; Ocak, Y.S.; Yakuphanoğlu, Fahrettin (Inderscience Publishers, 2013)
In this current work, we report on the surface morphology of pure (ZnO) and metal doped (MZO, M = Cu, Fe and Cd) zinc oxide nanostructures grown by sol-gel spin coating route onto a glass substrate at room temperature and speed of 1,000 rpm. We also investigate the effect of spinning speed on the physical and surface properties of coated ZnO films. The doping ratios Cu/Zn, Fe/Zn, Cd/Zn were kept at 2% in the solution. Atomic force microscope (AFM) revealed that nano-grains change in shape and growth orientation as a result of metal content. Average of grains sizes were found to be 87, 122, 174 and 260 nm respectively for pure, Cu, Fe and Cd doped ZnO. Based on the histogram profile, the shape looks like Gaussian curve for the pure ZnO, and it changes considerably for the M-doped ZnO films. Parameters of surface are investigated such as distribution of heights, power spectrum density (Psd), Fourier transform (Ft) of the picture and surface roughness (Rms). Spinning speed influences the surface and physical properties of coated ZnO films. The optimum results, high transparency (?72%) and low resistivity (9 k?cm), have been obtained with an increase in speed. Copyright © 2013 Inderscience Enterprises Ltd.
Keywords: AFM; Atomic force microscope; Grain size; Hall effect measurement system; HMS; Metal doping; Nanostructure; Resistivity; Spinning speed; Surface morphology; Transmittance; Zinc oxide; ZnO